Proceedings 10th IEEE International Conference on Networks (ICON 2002). Towards Network Superiority (Cat. No.02EX588)
DOI: 10.1109/icon.2002.1033281
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment of wavelength routed optical networks with shortest path routing over degree three topologies

Abstract: -In this paper, we present an assessment of the blocking performance in wavelength routing optical networks with degree-three topologies of minimum diameter. It is analysed a general family of degree-three topologies, of which the chordal ring family is a particular case. Performance results show that all topologies of absolute minimum diameter have exactly the same path blocking probabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…As described in section 2, the smallest diameter of an irregular degree-three topology is m+l, where m is obtained through equation 1. According to previous studies (see [15], [ 17]), the smallest diameter of a chordal ring is f i -1. Thus, the smallest diameter of the chordal ring with 100 nodes is 9, while the minimum of shortest path lengths in an irregular degree-three topology with 100 nodes is 6.…”
Section: Performance Assessmentmentioning
confidence: 98%
See 2 more Smart Citations
“…As described in section 2, the smallest diameter of an irregular degree-three topology is m+l, where m is obtained through equation 1. According to previous studies (see [15], [ 17]), the smallest diameter of a chordal ring is f i -1. Thus, the smallest diameter of the chordal ring with 100 nodes is 9, while the minimum of shortest path lengths in an irregular degree-three topology with 100 nodes is 6.…”
Section: Performance Assessmentmentioning
confidence: 98%
“…The two degreethree families previously studied, above referred, are subfamilies of this general family. For instance, the chordal ring family is the sub-family, of this general family, ..., DTT(N-I, N-3, w3) and we observed that each family of the type DTT(w1, (w1+2)madN, w3) or DTT(wl, (wl-2)mod N, w3), with 11wlS99 and wl#w2#w3, has a diameter which is a shifted version (with respect to w3) of the diameter of the chordal ring family [15]. We also identified the chord lengths at which minimum diameters occur.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In [8], we introduced a general family of degree three topologies, of which the chordal ring family is a particular case. In each node of a chordal ring, we have a link to the previous node, a link to the next node and a chord.…”
Section: Degree N Topologiesmentioning
confidence: 99%
“…In order to try to find degree three topologies that may outperform chordal rings with smallest diameter, in [8], we introduced a general regular degree three family, of which the chordal ring family is a particular case. We analysed all topologies of that general regular degree three family and we showed that there are several regular degree three topologies with the same smallest diameter of the chordal ring with smallest diameter and with exactly the same path blocking performance, but we have not found any degree three topology outperforming chordal rings with smallest diameter.…”
Section: Introductionmentioning
confidence: 99%